Does it pay to acquire technological firms? Motives, process and success of corporate acquisition ; experience of German-American firms - Alok K. Chakrabarti; Jürgen Hauschildt; Christian Süverkrüp (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1992)
Acquisition of corporation has always been an important activity in th U.S. and other countries. The motives for mergers have changed over time. Acquisition has become an important and quick means to gain access to technology and technological know-how. Acquisition of foreign firms has been an important instrument for foreign investment. Very little attention has been paid to strategic issues related to marketing and technology, and no attention has been paid to cross-national acquisitions. The paper focuses on several research questions: - – How do the firms differ in terms of their strategic objectives for foreign acquisitions? - What are the differences in the characteristics of firms following different strategies for acquisitions? - What are the determinants of "success" of acquisition when it is aimed at getting access to technology and know-how? - What are the differences between the American and German firms in terms of their acquisition strategies and successes? Our special interest was to get a closer look into the technological motive of the foreign acquisitions. The literature shows that technology is not unimportant, but it ranks only in the middle of the strategic considerations. Since technological knowledge is a long-term strategic variable, it seems to be underestimated in the empirical investigations. To find out about the technological motive we needed a two-step procedure...
Keywords: 650; Übernahme; Auslandsinvestition; Technologie; Deutschland; USA